2012
DOI: 10.3109/14767058.2012.704446
|View full text |Cite
|
Sign up to set email alerts
|

Average acceleration and deceleration capacity of fetal heart rate in normal pregnancy and in pregnancies complicated by fetal growth restriction

Abstract: Analysis of the AAC and ADC as recorded with a high resolution fECG recorder may differentiate better between normal and SFD fetuses than STV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 17 publications
1
63
1
Order By: Relevance
“…Dawes et al [17] defined a recording as sufficient for short-and long-term variability measurement if the recording had a high recording quality of ≥ 60%. First attempts to investigate fHRV by short-term variation using abdominal fECG were recently conducted in overnight recordings [18][19][20] . A new signal-processing technique, phase-rectified signal averaging, was used to minimize noise by averaging signals.…”
Section: Discussionmentioning
confidence: 99%
“…Dawes et al [17] defined a recording as sufficient for short-and long-term variability measurement if the recording had a high recording quality of ≥ 60%. First attempts to investigate fHRV by short-term variation using abdominal fECG were recently conducted in overnight recordings [18][19][20] . A new signal-processing technique, phase-rectified signal averaging, was used to minimize noise by averaging signals.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in fetal HRV is thought to indicate fetal compromise. Several studies have shown reduced HRV in growth-restricted fetuses compared to AGA peers, indicating that these fetuses are compromised by the unfavorable intrauterine environment (59)(60)(61)(62). Moreover, lowered HRV has been clearly associated with fetal acidemia and hypoxia (63).…”
Section: Hrv In Growth-restricted Fetuses and Infantsmentioning
confidence: 99%
“…A gradual reduction of fetal sympatho-vagal balance in the last trimester of healthy pregnancy was previously showed (21,22,23). The increased parasympathetic regulation was a sign of the fetal maturation in the late gestation.…”
Section: Discussionmentioning
confidence: 74%